2013
DOI: 10.1007/s00267-013-0140-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Natural and Anthropogenic Variability in Wetland Structure for Two Hydrogeomorphic Riverine Wetland Subclasses

Abstract: The hydrogeomorphic approach (HGM) to wetland classification and functional assessment has been applied regionally throughout the United States, but the ability of HGM functional assessment models to reflect wetland condition has limited verification. Our objective was to determine how variability derived from anthropogenic effects and natural variability impacted site assessment variables within regional wetland subclasses in central Oklahoma. We collected data for nine potential assessment variables includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Regional HGM subclasses offer better ecological resolution but were not used due to sample size limitations and the difficulty in characterizing and ascribing wetlands to subclasses in Oklahoma (Dvorett et al 2012). High climatic variability may also pose a challenge for wetland assessments in this region (Dvorett et al 2013), and we did not account (explicitly) for the wide range of precipitation across Oklahoma (Hoagland 2000). We did, however, split the Central Great Plains in western Oklahoma from ecoregions farther east, and we separated a drought/transitional period (2012-2013 surveys) from above-normal precipitation (2014-2015 surveys) across the region.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regional HGM subclasses offer better ecological resolution but were not used due to sample size limitations and the difficulty in characterizing and ascribing wetlands to subclasses in Oklahoma (Dvorett et al 2012). High climatic variability may also pose a challenge for wetland assessments in this region (Dvorett et al 2013), and we did not account (explicitly) for the wide range of precipitation across Oklahoma (Hoagland 2000). We did, however, split the Central Great Plains in western Oklahoma from ecoregions farther east, and we separated a drought/transitional period (2012-2013 surveys) from above-normal precipitation (2014-2015 surveys) across the region.…”
Section: Discussionmentioning
confidence: 97%
“…Crane (2014) similarly concluded that buffer metrics in the USA-RAM did not reliably predict vegetation diversity for Oklahoma depressional wetlands, and Bried et al (2014) showed mismatches between the USA-RAM buffer assessment and vegetation-based wetland quality classes in Oklahoma. Wetland assessment and classification in general appears to be challenging across Oklahoma due to a high degree of environmental and climatic variability (Hoagland 2000;Dvorett et al 2012Dvorett et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Following Dvorett et al (2013), we assigned a weighting coefficient (range: 0-1) to each of the 15 major land-use/land-cover (LULC) classes in the 2011 National Land Cover Dataset (NLCD) based on potential impacts to wetlands. We also calculated the combined percentage of altered land-use types (those with weighting coefficients <1; see Table 1 and Dvorett et al, 2013) at each buffer scale as a measure of anthropogenic disturbance. We also calculated the combined percentage of altered land-use types (those with weighting coefficients <1; see Table 1 and Dvorett et al, 2013) at each buffer scale as a measure of anthropogenic disturbance.…”
Section: Landscape Environmental Variablesmentioning
confidence: 99%
“…The loss of natural habitats due to the reclamation of land for urban and industrial development, agriculture and aquaculture has been substantial and continues to grow (Zhou et al, 2010;Prabhadevi and Reddy, 2012;Ottinger et al, 2013;Yuan et al, 2014). Like many other types of environment, riverine environments are affected by natural environmental changes, anthropogenic activities and synergistic interactions between the two (Smith et al, 2008;Euliss and Mushet, 2011;Dvorett et al, 2013).…”
Section: Introductionmentioning
confidence: 99%